Blood volume and hemoglobin mass in endurance athletes from moderate altitude - Schmidt, W.; Heinicke, K.; Rojas, J.; Manuel Gomez, J.; Serrato, M.; Mora, M.; Wolfarth, B.; Schmid, A.; Keul, J. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE To determine whether total hemoglobin (tHb) mass and total blood volume (BV) are influenced by training, by chronic altitude exposure, and possibly by the combination of both conditions.METHODS Four groups ( = 12, each) either from locations at sea level or at moderate altitude (2600 m) were investigated: 1) sea-level control group (UT-0 m), 2) altitude control group (UT-2600 m), 3) professional cyclists from sea level (C-0 m), and 4) professional cyclists from altitude (C-2600 m). All subjects from altitude were born at about 2600 m and lived all their lives (except during competitions at lower levels) at this altitude. tHb and BV were determined by the CO-rebreathing method.RESULTS [OV0312]O (mL.kg.min ) was significantly higher in UT-0 m (45.3 +/- 3.2) than in UT-2600 m (39.6 +/- 4.0) but did not differ between C-0 m (68.2 +/- 2.7) and C-2600 m (69.9 +/- 4.4). tHb (g.kg ) was affected by training (UT-0 m: 11.0 +/- 1.1, C-0 m: 15.4 +/- 1.3) and by altitude (UT-2600 m: 13.4 +/- 0.9) and showed both effects in C-2600 m (17.1 +/- 1.4). Because red cell volume showed a behavior similar to tHb and because plasma volume was not affected by altitude but by training, BV (mL.kg ) was increased in C-0 m (UT-0 m: 78.3 +/- 7.9; C-0 m: 107.0 +/- 6.2) and in UT-2600 m (88.2 +/- 4.8), showing highest values in the C-2600 m group (116.5 +/- 11.4).(2max)CONCLUSION In endurance athletes who are native to moderate altitude, tHb and BV were synergistically influenced by training and by altitude exposure, which is probably one important reason for their high performance.